Programming Arduino Next Steps Going Further with Sketches - Monk, Simon (McGraw-Hill Education, 2019)
Go beyond the basics with this up to date Arduino programming resource. Take your Arduino programming skills to the next level using the hands-on information contained in this thoroughly revised, easy to follow TAB guide. Aimed at programmers and hobbyists who have mastered the fundamentals, Programming Arduino Next Steps: Going Further with Sketches, Second Edition reveals professional programming tips and tricks. This up-to-date edition covers the Internet of Things (IoT) and features new chapters on interfacing your Arduino with other microcontrollers. You will get dozens of illustrated examples and downloadable code examples that clearly demonstrate each powerful technique.